Langmuir-Blodgett films of porphyrins and phthalocyanines - Portus, Dan (Cranfield University, 2002)
Phthalocyanines and porphyrins have been studied for many years as bulk, thick and thin films. Their use in Langmuir and Langmuir-Blodgett films is governed their peripheral substituents. These can enhance or reduce their ability to form "quality" ultra-thin films. There are a number of potential and current applications for thin films porphyrins and phthalocyanines, which include CD-R discs and gas-sensors. It is latter that this PhD has focussed on. Ultra-thin films of phthalocyanines, porphyrins and a porphyrin/phthalocyanine hybrid dye were deposited onto glass microscope slides, gold-coated glass microscope slides and quartz crystals. These assemblies were then characterised using Ultraviolet- Visible spectroscopy, pressure-area isotherms, surface plasmon resonance and a quartz crystal microbalance to try and determine the nature of the molecules on the surface the substrate. The thin films were exposed to chlorine gas and the change in their absorption spectrum and (in some cases) their surface plasmon resonance curve monitored. A short series of phthalocyanines showed that the central metal atom can play important role in the orientation of the macrocycles - with copper adopting an edge-configuration, zinc, face-down and metal-free, random. This in turn affected sensitivity of the gas-sensor with the facedown orientation offering a significantly greater response than the other two. A series of substituted tetraphenylporphyrins also illustrated that the sensitivity of the dye molecules is dependent on the orientation and spacing of molecules in the film. Generally the response to the chlorine was quite low, but porphyrin (stearamido) demonstrated a 2"d order decay in the absorbance due to oxidation of the macrocycle, the time constants being 31 and 425 seconds for surface and bulk diffusion responses respectively. The use of differentiation on the Pressure-Area Isotherms of the deposited Langmuir-Blodgett films is a new concept developed in this thesis. It proved a useful tool for looking at the effect of the quality of the film on the gas sensitivity.